The Role of Parents in Overcoming Juvenile Delinquency (Descriptive Study of Adolescents in Dilagusun Hamlet, Lamaksenulu Village Lamaknen District, Belu Regency) - Samrid Neonufa; Erni Raster Klau; Fredianus Dasi (Universitas Nusa Cendana, 2022)
ABSTRACT This thesis is entitled: